Measures taken by the hoteliers to overcome the COVID-19 impact / Noor Azimin Zainol, Nurhazani Mohd Shariff and Eshaby Mustafa - Zainol, Noor Azimin; Mohd Shariff, Nurhazani; Mustafa, Eshaby (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The hotel industry which supports the tourism industry, plays a crucial part in Malaysia's economic development. Unfortunately, the outbreak of COVID-19 had brought huge losses towards the tourism industry, both locally and globally in terms of cancellation of all related activities concerning travel and tours, including accommodation. Many researchers have attempted to highlight the effects of COVID-19 pandemic on various sectors, however limited studies have been conducted to address how the hospitality industry mitigate this situation to recover and revive the hospitality industry. Recent reported figures lack of empirical and academic underpinning. This paper aims to fill the gap. It is thus imperative to examine the measures being done by hoteliers in order to overcome this unprecedented scenario. Therefore, this study's aim is to highlight the measures taken by the hoteliers to overcome the ongoing COVID-19 impact in terms of staff employment, working terms and hotels' loss of revenue. A qualitative research was deemed applicable to be conducted to investigate this scenario. The data collection was founded based on the Grounded Theory approach and feedback was collected through semi-structured interviews among 15 staffs from the Food and Beverage, Accounts and Front Office departments which were selected using purposive sampling from five different hotels in Penang. The findings showed that all informants have come to the agreement that the measures taken by their hotels to overcome the COVID19 impacts in terms of staff employment and working terms was to lower down the hotel operation cost. This was done by reducing the number of employees and also reducing staffs' salaries. Apart from that, other measures taken by the hotel management to overcome the pandemic's impact include increasing room sales, venturing into other services, and extending bookings for events. The findings of this study have some practical implication towards fellow hoteliers as they could adopt similar strategies in their respective hotels in coping with impacts of COVID-19.